THE RATE OF RENAL DYSFUNCTION IN PATIENTS WITH ACUTE CORONARY SYNDROME AFTER USING X-RAY CONTRAST AGENTS - N. T. Vatutin; M. I. Zinkovych (Медицинский вестник Юга России, 2015)
Purpose: to evaluate the rate and severity of filtration renal dysfunction in patients with acute coronary syndrome after percutaneous coronary intervention (PCI) with X-ray contrast.Materials and Methods: serum creatinine levels were collected from 71 patients twice, before the introduction of the contrast agent and 3 days.Resuls: in 56.9% of cases was recorded worsening renal function, and in 37.3% diagnosed the incidence of contrast-induced nephropathy (CIN), defined as a rise in serum creatinine level by 25% or more.Summary: because at the time of admission to the hospital, a physician still does not have enough reliable criteria for evaluating the risk of CIN, a preventive measures for improving renal function have to be included in the complex treatment of patients who are receiving the radiocontrast agent. Regardless of the severity of patients’ condition and the presence of concomitant chronic diseases.